2014
DOI: 10.1186/2050-5736-2-12
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided high-focused ultrasound for renal sympathetic denervation—a feasibility study in pigs

Abstract: BackgroundRenal sympathetic denervation has recently gained clinical relevance for the treatment of therapy-resistant hypertension. Denervation is currently mainly performed using catheter-based transarterial radiofrequency ablation of periarterial sympathetic nerve fibers. Since this approach has numerous limitations, we conducted a study to evaluate the feasibility, safety, and efficacy of magnetic resonance-guided high-focused ultrasound (MRgHiFUS) for renal sympathetic denervation in pigs as an alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
8
0
5
Order By: Relevance
“…Therefore, while MR thermometry was not able to predict an acute treatment assessment, the use of the temperature probe did demonstrate the MRgHIFU beam was focused in close proximity to the renal artery. This result extends the assessment that has been performed in other HIFU RSD studies [ 13 , 12 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Therefore, while MR thermometry was not able to predict an acute treatment assessment, the use of the temperature probe did demonstrate the MRgHIFU beam was focused in close proximity to the renal artery. This result extends the assessment that has been performed in other HIFU RSD studies [ 13 , 12 ].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the total delivered energy per animal varied from 10–100 kJ. Other RSD HIFU studies reported total energy delivery of 18 kJ [ 12 ] and a mean of 26.2 kJ per animal [ 13 ] with varied efficacy results. This variability indicates that successful treatment outcome is a function of applied dose as well as animal position and size.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Current clinical applications of MRgHIFU include the ablation of tumors [1619], functional neurosurgery [20] and palliation of pain in patients with bone metastasis [21]. The lowered risk of complications due to the noninvasive nature of MRgHIFU makes it an attractive modality for neurolysis [2224]. …”
Section: Introductionmentioning
confidence: 99%